DEVELOPMENT OF INSTRUMENTS FOR ASSESSING CRITICAL THINKING SKILLS OF HIGH SCHOOL STUDENTS IN SOUND WAVE MATERIAL - Rahmayani, Pepi; Bunawan, Wawan (IPER (Indonesian Physics Education Research), 2024)
This study aims to obtain the innovation of sound wave material assessment instruments, and obtain instruments of assessment of critical thinking skills that meet valid and reliable criteria. This type of research is ADDIE. Product development procedures through the analysis research stage to implementation. At the analysis stage, the preliminary stage includes analysis of the types of instruments found in the school. Design procedures, namely the stage of compiling questions to form questions, at the development stage is the stage of formulating the type of instrument, validation to experts, limited trials, large-scale trials and product implementation. The results of this study are the types of assessment instruments developed are essay test analysis, problem solving tests that are oriented towards students' critical thinking skills applied in the SMA 2 Percut Sei Tuan high school. Instruments are declared valid and reliable. The instrument can measure the average student learning outcomes, measuring the proportion of student completeness.